Conceptual design for multi terrain mobile robot - Tan, Chee Fai; Sarban Singh, Ranjit Singh; Karjanto, Juffrizal; Md. Yusof, Nidzamuddin; Khalil, Siti Nurhaida; Dhar Malingam, Sivakumar; E.S. Ng; Chen, Wei; Rauterberg, Matthias; Lim, Danny Thiam Lai (Australian Journal of Basic and Applied Sciences (AJBAS), 2013)
This paper presents the conceptual design of the multi terrain mobile robot with total design approach. Twenty conceptual designs were generated for selection purpose. To determine the final design of multi terrain mobile robot, the matrix evaluation method was used. The weight of the concept was obtained through weighted analysis. The final design of the multi terrain mobile robot is the mobile robot with six independent motorized wheels. The mobile robot has a steering wheel in the front and the rear, and two wheels arranged on a bogie on each side. Each wheel can operate separately on different type of terrain. Twenty conceptual designs were generated for selection. To determine the final design of multi terrain mobile robot, the matrix evaluation method was used. The weight of the concept was obtained through weight analysis.